Common sleep disorders in pregnancy: a review - Kember, Allan J.; Elangainesan, Praniya; Ferraro, Zachary M.; Jones, Claire; Hobson, Sebastian R. (Frontiers in Medicine, 2023)
In this review, we provide a comprehensive overview of common sleep disorders during pregnancy, including their characterization, prevalence, risk factors, and possible contribution to maternal and fetal outcomes. We conducted a quasi-systematic literature search of the MEDLINE database and identified 744 studies from 1991 through 2021, inclusive, that met our inclusion criteria. We synthesized the existing literature on sleep disorders during pregnancy and highlighted controversies, research gaps, and needed clinical developments. Our review covers a range of sleep disorders, including insomnia, obstructive sleep apnea, restless legs syndrome, and circadian rhythm disorders. We discuss the prevalence of these disorders in pregnancy and their potential impact on maternal and fetal health outcomes. We also explore the relationship between sleep disorders, pre-pregnancy comorbidities such as obesity, and pregnancy-related conditions such as gestational diabetes mellitus and preeclampsia. In addition to summarizing the existing literature on sleep disorders during pregnancy, we also highlight opportunities for further research in this area. We suggest that future studies should strive to employ validated and objective measurement tools for sleep disorders and prioritize utilization of longitudinal methods with participant follow-up through postpartum, mid-life, menopause, and beyond. We also put forward investigation into the impact of circadian rhythm disruption on reproductive physiology and early pregnancy outcomes as an area of important work. Overall, our review provides valuable insights on sleep and reproduction and into common sleep disorders during pregnancy and their potential impact on maternal and fetal health outcomes.